(untitled) (Research, Society and Development, 2021)
Objective: to report the routine of the Nursing teams in the care of patients undergoing electroconvulsive therapy. Results: electroconvulsive therapy is a procedure performed in an outpatient surgery center for psychiatric treatments, being, in some cases, the last intervention in severe and refractory disorders. It is performed three times a week, from Monday to Friday, with a one-day break between sessions; 15 patients per day are scheduled. Due to COVID-19, there was a reduction to eight patients per day. The team is composed of Psychiatric and Surgical Nurses and Psychiatry and Anesthesiology doctors. The procedure requires specific safety measures, such as an eight-hour fast. Such care, typical of Nursing, gains special plot in severe psychiatric patients. Controlling the ingestion of food and water in globally disoriented patients and those at risk of aggression due to delirium is only one of the challenges. The procedure is only performed after the conditions of relaxation and anesthesia have been met with the release of the electromagnetic wave stimulation. The main complications in the recovery room are related to hypoventilation. Final considerations: it is important to emphasize the importance of Nursing in terms of the integrality of care, evidenced by its continuous presence before, during and after the performance of this procedure.